1996
DOI: 10.1590/s0102-311x1996000400015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the copepod Mesocyclops longisetus (Crustacea: Cyclopidae) on the survival of Vibrio cholerae O1 in fresh water

Abstract: In an experimental microcosm, an analysis was performed of the influence exerted by freshwater Mesocyclops longisetus copepods on the survival of Vibrio cholerae O1 serovar Inaba. In the State of Ceará, copepods are used in the control of Aedes aegypti larvae. The system consisted of water with a salinity of 0.27 per 10,000 habitants and pH 7.5, which after sterilizing filtration was distributed into seven flasks with a volume of 400 ml; in each of six flasks, 10 live copepods were inoculated along with 1 ml o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
1
0
3
Order By: Relevance
“…2) Elevada umidade absoluta. Sem dúvida que outros parâmetros também estão associados ao processo, como o número excessivo de excretores fecais de V. cholerae O 1 na fase epidêmica, contaminando ecossistemas aquáticos, onde o fito e zooplanctons, como certas algas, possibilitariam a sobrevivência e multiplicação da bactéria no período silente (Islam et al, 1993(Islam et al, , 1994Araújo et al, 1996).…”
Section: Discussionunclassified
“…2) Elevada umidade absoluta. Sem dúvida que outros parâmetros também estão associados ao processo, como o número excessivo de excretores fecais de V. cholerae O 1 na fase epidêmica, contaminando ecossistemas aquáticos, onde o fito e zooplanctons, como certas algas, possibilitariam a sobrevivência e multiplicação da bactéria no período silente (Islam et al, 1993(Islam et al, , 1994Araújo et al, 1996).…”
Section: Discussionunclassified
“…Araújo et al [79] examined the influence of the copepod Mesocyclops longisetus on the survival of V. cholerae O1 serovar Inaba in freshwater. The study confirmed a clear association between V. cholerae O1 and live copepods, as the bacteria survived at compatible levels with the initial inoculation for six days in the presence of copepods.…”
Section: Pathogen Bacteria Associated With Copepodsmentioning
confidence: 99%
“…in estuarine and coastal environments [60], including the human pathogens V. parahaemolyticus, V. alginolyticus, V. vulnificus, and V. cholerae [61,62]. The adhesion of V. cholerae to live copepods has been demonstrated to extend its survival and culturability in both marine and fresh water when compared to adhesion to dead copepods, or free-living cells [63], suggesting that copepods may function as environmental reservoirs for the pathogen [64]. The pathogenic impact of associations with Vibrio spp.…”
Section: Bacterial Symbionts Of Copepodsmentioning
confidence: 99%